Pengukuran Tingkat Kesadaran Keamanan Siber di Kalangan Mahasiswa saat Study From Home dengan Multiple Criteria Decision Analysis (MCDA) - Andriani Kusumaningrum; Hendro Wijayanto; Bayu Dwi Raharja (STMIK Sinar Nusantara, 2022)
Covid-19 pandemic has forced all sectors to be online. Likewise in higher education, college students must carry out their learning activities from home and use computer information technology. This high digital activity will make cyber-crime high. Measurement of cybersecurity awareness for students when studying from home can be a reference to educate students on the importance of cybersecurity. Its measurement used multiple criteria decision analysis or MCDA. Multi-criteria decision analysis (MCDA) is one of the elements risk managements contained in SNI ISO 31000. The measured dimensions were knowledge, attitude and behavior within areas of using passwords, email and internet, mobile devices, social media, incidents and consequences. The calculation of the weighting used the analytic hierachy process or AHP method. The results of the measurements showed a total value of 79.5% or entered at a moderate level. At this level, students already have good knowledge of cybersecurity readiness. However, students have not been maximal in applying it to their daily activities. The assessment of the knowledge dimension showed a value of 84%, attitude of 78.3% and behavior of 73.1%. It needs to be an increase in socialization in terms of cybersecurity. This result was 8.5% difference from previous research with different object and question components. It still showed the level of awareness at the level of